2014
DOI: 10.4149/bll_2014_017
|View full text |Cite
|
Sign up to set email alerts
|

Treatment difficulty with acute GVHD – frequent cause of mortality after allogeneic hematopoietic stem cell transplantation

Abstract: Abstract:Objective: Acute graft-versus-host disease (aGvHD) remains a signifi cant cause of morbidity and mortality after allogeneic hematopoietic stem cell transplantation (HSCT). Methods: In this study, we have retrospectively evaluated the major risk factors for the development of aGvHD in 100 patients who underwent allogeneic transplantation at the University Hospital in Bratislava between January 2007 and December 2011. Results: 29 patients acquired acute GvHD (Grade I -12 patients, G II -5 , G III -3, G … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…9,10 Graft-versushost disease prevention is based on pre-and post-transplantation pharmacological immunosuppression or graft engineering, such as T lymphocyte depletion. The GvHD first-line treatment consists of steroids and calcineurin inhibitors (CNIs), 11 but up to 50% of patients with aGvHD do not respond to this therapy. 12 In steroid-resistant (SR) aGvHD, multiple therapies have been studied, ranging from high-dose steroids to mono-and polyclonal antibodies (basiliximab, daclizumab, etanercept, anti-thymocyte globulin (ATG), infliximab), extracorporeal photopheresis (ECP), or cellular therapies with mesenchymal stem cells (MSCs).…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Graft-versushost disease prevention is based on pre-and post-transplantation pharmacological immunosuppression or graft engineering, such as T lymphocyte depletion. The GvHD first-line treatment consists of steroids and calcineurin inhibitors (CNIs), 11 but up to 50% of patients with aGvHD do not respond to this therapy. 12 In steroid-resistant (SR) aGvHD, multiple therapies have been studied, ranging from high-dose steroids to mono-and polyclonal antibodies (basiliximab, daclizumab, etanercept, anti-thymocyte globulin (ATG), infliximab), extracorporeal photopheresis (ECP), or cellular therapies with mesenchymal stem cells (MSCs).…”
Section: Introductionmentioning
confidence: 99%
“…As neurological improvement correlates to the level of enzyme secretion [14,19] the higher level of enzyme production by MSCs has the potential to allow more widespread GAG clearance than HSC therapy. Together with the inherent properties of MSCs the results presented here suggest that they be investigated as a therapy for MPS disease either as a standalone approach or as an adjunct to HSC therapy to alleviate GvHD and improve GAG clearance [81,82].…”
Section: Discussionmentioning
confidence: 91%
“…In particular, their ability to form multiple cell types in vitro [20][21][22][23]26] and in vivo [77][78][79], their ability to cross the BBB [80], and their ability to inhibit T-cell proliferation and hence lower the immune response of the host [81,82] are pertinent to the treatment of MPS disease. In this study we have shown that MSCs produce and secrete multiple different MPS enzymes, they are readily transducible, transduction is stable with cell division and does not inhibit their ability to differentiate down multiple lineages in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Steroids and calcineurin inhibitor (CI) remain the gold standard for initial treatment of aGVHD (15). Mild skin aGVHD (grade I) can be treated with topical steroids alone.…”
Section: Treatment Of Agvhdmentioning
confidence: 99%